Toward Fluent Speaking: Spoken Grammar Instruction in EFL Classrooms - Nguyen, Thao (Issues in Language Instruction, 2018)
Grammar teaching in EFL classrooms is high-stakes, which can raise anxiety when students try to speak. This also results in their lack of natural and authentic English. The presenter introduces an effective way to help students decrease such anxiety to enhance confidence for more fluency in real-life conversations